Pernicious anemia: a myelodysplastic syndrome look-alike - Yazeed Kesbeh; Zahra Pakbaz (Greater Baltimore Medical Center, 2019)
Severe cytopenias (anemia, thrombocytopenia, neutropenia or any combination of these) are common causes of ER visits and hospital admissions. In adults, the etiology of cytopenias has a broad differential diagnosis including vitamin and mineral deficiencies, autoimmune conditions, infections, bone marrow failure disorders, or malignancies. We present a case of severe anemia and thrombocytopenia who was initially diagnosed with myelodysplastic syndrome (MDS) based on the results of a bone marrow biopsy. However, subsequent workup revealed that she had B12 deficiency secondary to pernicious anemia. This case highlights how performing a bone marrow biopsy without investigating secondary causes of cytopenia and bone marrow dysplasia can lead to a false diagnosis of MDS. Confirmation of the appropriate diagnosis spared the patient emotional trauma and unnecessary treatment with hypomethylating agents.